High Entrainment Constrains Synaptic Depression Levels of an In vivo Globular Bushy Cell Model - Rudnicki, Marek; Hemmert, Werner (Frontiers in Computational Neuroscience, 2017)
Globular bushy cells (GBCs) located in the ventral cochlear nucleus are an essential part of the sound localization pathway in the mammalian auditory system. They receive inputs directly from the auditory nerve and are particularly sensitive to temporal cues due to their synaptic and membrane specializations. GBCs act as coincidence detectors for incoming spikes through large synapses—endbulbs of Held—which connect to their soma. Since endbulbs of Held are an integral part of the auditory information conveying and processing pathway, they were extensively studied. Virtually all in vitro studies showed large synaptic depression, but on the other hand a few in vivo studies showed relatively small depression. It is also still not well understood how synaptic properties functionally influence firing properties of GBCs. Here we show how different levels of synaptic depression shape firing properties of GBCs in in vivo-like conditions using computer simulations. We analyzed how an interplay of synaptic depression (0 % to 70 %) and the number of auditory nerve fiber inputs (10 to 70) contributes to the variability of the experimental data from previous studies. We predict that the majority of synapses of GBCs with high CFs (>500 Hz) have a rate dependent depression of less than 20 %. GBCs with lower CF (<500 Hz) work also with strong depressing synapses (up to 50 % or more). We also showed that synapses explicitly fitted to in vitro experiments with paired-pulse stimuli did not operate properly in in vivo-like conditions and required further extension to capture the differences between in vitro and in vivo experimental conditions. Overall, this study helps to understand how synaptic properties shape temporal processing in the auditory system. It also integrates, compares, and reconciles results of various experimental studies.